Phulābaṛī, itihāsa khyāta ekaṭi grāma - Caudhurī, Mustānachirura Rahamāna; Caudhurī, Phakharula Isalāma (Sileṭa : Mustānachirura Rahamāna Caudhurī ; [Ḍhākā] : Prāptisthāna National Library, 1992)
History of Phulabāṛī, a historically important village in Sylhet District, Bangladesh; includes genealogical tables.
In Bengali.
Includes bibliographical references (prelim. p. [14]).
committed to retain
Keywords: Phulabāṛī (Bangladesh) -- History; Bangladesh -- Phulabāṛī (Sylhet District); History